Reformasi Pendidikan Agama Islam Di Indonesia di Era Millennial - Wibowo, Raditya; Muhammad Iqbal Khalid; Dinda Rizkina Fadhilah; Isnaini Nasabilah Zahrani; Farell Gymnastiar Ramadhan; Aditia Muhammad (Universitas Nahdlatul Ulama Sunan Giri, 2025)
As the nation with the biggest Muslim population in the world, Indonesia places a high priority on Islamic religious education. However, the implementation of Islamic religious education in Indonesia still faces many obstacles in this millennial era. Reform of Islamic religious education in Indonesia needs to be implemented. At the beginning of the 20th century, ideas for the renewal or reform of Islamic education emerged in Indonesia. This inspiration arose because more and more people were dissatisfied with the education system that was in effect at the time. Therefore, there are things that need to be addressed, namely in terms of content or materials, methods, and management of education. Islamic Education Reform in Indonesia in the Millennial Generation Era has been a hot topic of discussion lately. This research aims to discuss the challenges and opportunities faced in responding to the increasingly complex and diverse needs of Islamic religious education for the millennial generation. Islamic religious education in Indonesia has a very crucial role in shaping the character of today's youth besides cultivating scientific skills. Reform of Islamic Education in Indonesia in the era of the millennial generation is needed to build a generation that has good morals and Islamic character. Therefore, Islamic religious education in Indonesia must be made a top priority. Islamic religious education is expected to form well-educated students who use Islamic religious teachings, are able to apply them to everyday life, and contribute to forming a more moral society and shaping the resilience of Muslims in an increasingly complex world.